Leap of Faith in Leap Beyond - Laine, Verna (My University, 2020)
In this thesis the author introduces a concept (leap of faith) and traces back its practical application as an artistic-pedagogical premise and method in the making of a performance (Leap Beyond). The central concept and the concepts surrounding it have been explored by the author previously in another artistic research context (wherein the author theorised a possible approach to actor movement training based on the concept of a leap of faith) and have been expanded and explored further in this thesis. The thesis focuses around two questions: 1) How do I (the author) as an art pedagogue implement ideas of Leap of Faith in a rehearsal process for a performance? 2) What kind of pedagogy does this call forth? The first question allows the author to map out the training and rehearsal process towards the performance Leap Beyond in the light of the concept of a leap of faith and relate them with the surrounding concepts of anxiety, the unknown and that-which-is-not-yet. The surrounding concepts enable the author to contextualise and place the work within a larger discourse on art practice, art pedagogy and learning. The author presents and outlines the practical application and means with which the implementation of ideas of a leap of faith was made, with specific focus on the aerial work and the developments towards it. The second question acts as a follow-up question that opens up possibilities for further investigation in the future. It allows the author to reflect on the pedagogical choices that were made before and during the process. Through the second question it also becomes possible for the author to reflect on features about the work that have clarified their meaning to the author only after the official part of the production process had come to an end. The author concludes the thesis by proposing potential future developments and prospects.
Keywords: Leap of faith; Qualitative leap; Anxiety; tuntematon; okänslig; Art practice; Theatre pedagogy; Disobedient pedagogy; Aerial work; Aerial theatre; Aerial dance; Movement pedagogy; Body practices; Trust; Unknown.; Pedagogy; Skills training; Movement.; Risk.; taidepedagogiikka; liike; riskinotto; luottamus; konstpedagogik; rörelse; risktagande; förtroende; fi=teatteriopettaja|sv=teaterpedagogik|en=Theatre Pedagogy|